Lung B cells in ectopic germinal centers undergo affinity maturation - Stephane M. Guillaume; William S. Foster; Isabel San Martín Molina; Emily M. Watson; Silvia Innocentin; Grant M. Kennedy; Alice E. Denton; Michelle A. Linterman (Proceedings of the National Academy of Sciences, 2025)
The lungs are constantly exposed to the external environment and a myriad of antigenic challenges within the air. Chronic exposure to allergens and other airborne antigens can result in the formation of lymphocyte aggregates in the lung, which can harbor ectopic germinal centers (GCs). After allergen exposure, GCs that form in the lung are much smaller and less densely packed with B cells than lymph node GCs. Despite this, ectopic lung GCs support somatic hypermutation and affinity-based maturation as in lymph node GCs, and export memory B cells (MBCs) directly into the lung tissue. This demonstrates that the lung can locally diversify B cell responses and supports the generation of tissue MBC populations in situ.